THE ROLE OF PARENTS IN TAKING TIME FOR CHILDREN'S LEARNING ASSISTANCE IN BIDUK-BIDUK KAMPUNG - Farahnaz, Filza; Wingkolatin, Wingkolatin; Marwiah, Marwiah (Unmul Civic Education Journal, 2021)
The Role of Parents in Taking Time to Assist Children in Learning in the Big Dipper Village. The purpose of this study was to find out how the role of parents in taking the time to assist children's learning in the Biduk-Biduk village and what factors influence the efforts that parents make. This research uses a qualitative descriptive research type. This research was conducted from March to May 2022. The research subjects were parents and grade IX students of SMP Negeri 1 Biduk-Biduk. Data collection techniques using observation, interviews, and documentation. Data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions or verification. Based on the results of the study, it is shown that the role of parents in taking the time to assist children in learning in Biduk-Biduk Village is very important, this can be seen from the magnitude of the impact on children in the learning process, this is to support children's learning enthusiasm, with parents carrying out their role functions. properly, it makes children more motivated, and disciplined and increases their enthusiasm for learning themselves.